Ethnobotanical heritage: Medicinal plants in Mogi das Cruzes-SP (Research, Society and Development, 2022)
This paper presents a study about medicinal plants in Mogi das Cruzes and their uses in home remedies are studied. The objective of this work is to raise knowledge about the medicinal plants used by the population of the city of Mogi das Cruzes, SP. This is a descriptive study with a cross-sectional qualitative approach. One hundred citizens living in Mogi das Cruzes participated, from August to September 2019. Data collection was carried out through a questionnaire to identify the types of medicinal plants known and used by the population and the purpose of each use. The results showed that 66.5% of the participants use plants for medicinal purposes, and the majority (71.21%) use them from vegetable gardens or backyards in their homes. 73 species were mentioned, distributed in 35 families. The most cited plants for medicinal purposes were melissa (Melissa officinalis L., cited 19 times), boldo (Plectranthus barbatus Andr., 13), kale (Brassica oleracea L., 10), rosemary (Rosmarinus officinalis L., 7), chamomile (Chamomilla recutita L., 7), guaco (Mikania glomerata Spreng, 7), pennyroyal (Mentha pulegium L., 7), orange (Citrus sp., 6), parsley (Petroselium crispum (Mill) Nym, 5) and the white rose (Rosa alba L., 4). Most use it in recipes like teas, followed by bath, juice and syrup. The use of medicinal plants requires time and knowledge; this practice can contribute to biodiversity conservation and its dissemination to each generation promotes the preservation of a local culture.